Activity of gallic acid and its ester derivatives in Caenorhabditis elegans and zebrafish (Danio rerio) models - Singulani, Junya De Lacorte [UNESP]; Scorzoni, Liliana [UNESP]; Gomes, Paulo César [UNESP]; Nazaré, Ana Carolina [UNESP]; Polaquini, Carlos Roberto [UNESP]; Regasini, Luis Octávio [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Taylor & Francis, 2017)
Aim: Gallic acid and its ester derivatives have shown antifungal activity in vitro. This study was performed to investigate their activity against Candida albicans and their toxicity in the animal models Caenorhabditis elegans and zebrafish embryos. Results: The compounds protected worms from C. albicans infection. The dodecyl gallate was the most effective. In zebrafish embryo, gallic acid and dodecyl gallate were the least toxic. Conclusion: Gallic acid and its ester derivatives have potential for in vivo use against C. albicans infection. The antifungal effects and toxicity of gallate esters in these alternative animal models were dependent on carbon chain length.
Keywords: alternative animal models; antifungal development; gallates; gallic acid; infection